Composição florística de plantas espontânea em sistema de plantio direto na capoeira triturada e corte e queima - Marques, Luiz Junior Pereira (2010)
The system of slash and burning is a practice that degraded natural resources but is common in tropical regions due to the tradition of the farmer. To replace the slash and burning several projects are being developed as the no-tillage system in secondary vegetation. Weeds are an obstacle in agricultural production, being widely studied in conventional agriculture and few studies in the systems of family farming. The aim of this study is to survey the flora of weeds in the area of no tillage in the secondary forest cultivated with cowpea and burned area cultivated with cowpea and cassava for two and three agriculture years respectively. The search was conducted in area chop with implement a coupled (Ahwi FM600) a tractor wheels. In the first (2006/2007) and second crop year (2007/2008) the chop area was cultivated with maize following BRS Guariba cowpea. The burned area was prepared by cutting and burning of secondary vegetation followed by planting of maize and cowpea succession. In the two years following agricultural, the area burned was prepared by plowing and subsequently xiv cultivated with maize and cassava succession (2007/2008) and cowpea (2008/2009). The collection of weeds was realized at 30 and 60 days after the sown of culture with a rectangle (0.5 m x 0.3 m) randomly released 30 times in the chop area and 10 times in the burned area. With each release, the aerial parts of weeds were harvested, counted and identified. The dry mass was quantified after maintenance in the greenhouse with forced ventilation of air at 70° C, until constant weight. With these data was calculated phytosociological index (relatively frequency, density, dominance and importance value index). The main weeds in chop area were Cyperus diffusus that prevailed for two years and Digitaria horizontalis only in second year. In the burned area, the species of highest importance value were Imperata brasiliensis, Sida glomerata after burner, Spermacoce verticillata, Juncus sp. and Cyperus sp. after plowing. The secondary vegetation plants have been reduced dramatically in both the system of land use, therefore, in slash and burning the reduction was more pronounced in the first year of cultivation. The study also finds that the management tillage practices and crop rotation change the floristic composition with the time